ChatGPT dalam Dunia Virtual: Eksplorasi Pemanfaatan AI dalam Lingkungan Pembelajaran Mahasiswa - Mutmainnah; Nurul Azizah; Putri Nirmala; Hajar Dewantara; Andika Isma (Journal of Vocational, Informatics and Computer Education, 2025)
The rapid development of information and communication technology presents challenges in higher education, particularly regarding students’ limited understanding of how to effectively integrate emerging tools like ChatGPT and Metaverse into learning. This study aims to explore students’ perceptions of ChatGPT utilization within the Metaverse learning environment at Universitas Negeri Makassar. A mixed-method approach was applied by distributing online questionnaires to 60 students across various cohorts and conducting interviews with selected respondents. The findings reveal that most students perceive ChatGPT positively, with 56% rating it effective in supporting learning, 58% expressing comfort in using it for academic tasks, and over 70% acknowledging its role in enhancing learning efficiency, critical thinking, and confidence in discussions. Moreover, ChatGPT was reported to improve access to learning resources, problem-solving in academic tasks, and overall learning quality, despite some students facing minor challenges in adoption. These results suggest that ChatGPT, when integrated into Metaverse-based learning, has significant potential to enhance educational outcomes, provided institutions offer proper guidance and support to maximize its benefits.